MAQĀMĀT DALAM MANTHIQ AL-THAYR AL-ATTĀR - Syamsun Ni’am (Sekolah Tinggi Agama Islam Sadra, 2015)
Attār is one to be accounted amongst the greatest sufi poets of Persia sufis in the history of Sufism who has notable contibution to the esoteric Islam (Sufism). He packed his mystical teachings in the form of poetry and verse, -to be more interactive and expressive- though his teachings are not different with his predecessors, particularly of those who inspired by the principle of mystical union; and Attār is among the Sufis who have managed to reach the highest peak in the mystical journey. According to Attār , there are seven valleys that must be passed by spiritual traveler (sālik) in his mystical journey, as mentioned in Manthiq al-Thayr. In this work he use the language of poetry to reveal the process of a servant to God through the stages (maqāmāt), and Attār gives the parable maqāmāt is like a bird -burung flying looking for the king. Attār call maqāmāt is the term valleys, of which there are seven valleys.